Thermogravimetric studies of a nasal preparation with an interleukin-1β (IL-1Ra) antagonist - B. S. Burlaka (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Interleukin-1 receptor antagonist (IL-1Ra) is an active pharmaceutical ingredient obtained by the method of gene transformation of Escherichia coli, provides a neuroprotective effect, namely – inhibition of oxidative modification of proteins, normalization of functional activity of mitochondrial energy, mitochondrial energy. Early complex physical-chemical, microbiological, and biopharmaceutical studies have developed a new intranasal formulation, the formulation of which contains: IL-1Ra, sodium carboxymethyl cellulose, D-panthenol, benzalkonium chloride, trilon B, Tween-80, phosphate buffer solution. Given the peculiarities of the technological process, when creating a new gel dosage form, it is necessary to justify the temperature of the carrier base, the introduction of the active substance into the base, as well as to predict the possible chemical interaction of individual components in the dosage form. Therefore, the application of thermogravimetric analysis in pharmaceutical technology is relevant.